La actividad turística en la UE antes y después de la pandemia: el drama de España - Gago de Santos, Pilar (Papeles de Europa, 2022)
Before the 2020 pandemic, the travel and tourism sector was a key driver in the world economy. Europe and the EU in particular, along with the United Kingdom obtained the lion share of the international demand of tourism in terms of international arrivals and receipts from inbound tourism. In this paper, we explain the relevance ot the travel and tourism sector for the EU and the diferential impact produced by the pandemic, compared with other world markets impact. The case of Spain is highlighted